Claimability Of Illegal Earnings In Tort: A Perpetual Case For Equity To Intervene - Ahangar, Muhammad Altaf Hussain (Journal of Malaysian and Comparative Law, 1999)
Loss of earnings is one of the heads of damages allowed by tort law in relation to personal injury and fatal accident claims.